Controle remoto e segunda tela para uma TV 3.0 orientada a aplicativos - Pernisa Júnior, Carlos; Moreno, Marcelo F.; Teixeira, Stanley Cunha; Montezano, Cristiane Turnes (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This paper explores the innovations proposed for TV 3.0, with a focus on the development of a reference remote control and the integration of the second screen. The remote control, redesigned for this new ecosystem, includes advanced functionalities that extend to second-screen devices, such as smartphones. The second screen, in addition to replicating the remote control, enhances interaction possibilities with features like content personalization, real-time synchronization, and improved accessibility. Detailed use cases include navigating program guides, marking and zooming in on specific areas during sports broadcasts, controlling ambient stadium sound, and managing profiles and privacy directly on the second screen. These examples illustrate the potential of TV 3.0 to offer a rich and adaptable experience for diverse audiences.